Kinetically Differentiating Influenza Hemagglutinin Fusion and Hemifusion Machines - Mittal, Aditya (Biophysical Society, 2003)
Membrane fusion mediated by influenza virus hemagglutinin (HA) yields different phenotypes depending on the surface density of activated HAs. A key question is whether different phenotypes arise from different fusion machines or whether different numbers of identical fusion machines yield different probabilistic outcomes. If fusion were simply a less probable event than hemifusion, requiring a larger number of identical fusion machines to occur first, then two predictions can be made. First, fusion should have a shorter average delay time than hemifusion, since there are more machines. Second, fusion should have a longer execution time of lipid mixing after it begins than hemifusion, since the full event cannot be faster than the partial event. Using a new automated video microscopy technique, we simultaneously monitored many HA-expressing cells fusing with erythrocytes and identified individual cell pairs with either full or only partial redistribution of fluorescent lipids. The full lipid mixing phenotype also showed contents mixing, i.e., fusion. Kinetic screening of the digitized fluorescence data showed that the execution of lipid mixing after the onset is faster for fusion than hemifusion. We found no correlation between the delay times before the onset of lipid mixing and the final fusion phenotype. We also found that the execution time for fusion was faster than that for hemifusion. Thus, we provide the first experimental evidence for fusion and hemifusion arising from different machines.